2014
DOI: 10.1089/cell.2014.0054
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Profiles of Induced Neurons Converted Directly from Adult Human Fibroblasts Indicate Incomplete Neuronal Conversion

Abstract: The direct conversion of human fibroblasts to neuronal cells, termed human induced neuronal (hiN) cells, has great potential for future clinical advances. However, previous studies have not provided an in-depth analysis of electrophysiological properties of adult fibroblast-derived hiN cultures. We have examined the electrophysiological profile of hiN cells by measuring passive and active membrane properties, as well as spontaneous and evoked neurotransmission. We found that hiN cells exhibited passive membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Throughout all reported studies, induced neuronal cell functionality has been confirmed by electrophysiological analysis. Interestingly, a recent in-depth examination of the electrophysiological profiles of human induced neuronal cells generated by lentiviral vector expression of BAM, Olig2, and Zic1 has revealed that the conversion of fibroblasts to neuronlike cells is incomplete, with passive membrane properties comparable to that of highly immature neurons [86] . However, the induced neuronal cells used in this study were sourced from research that has since been retracted, thus questioning the validity of these results.…”
Section: Generation Of Induced Neuronal Cellsmentioning
confidence: 99%
“…Throughout all reported studies, induced neuronal cell functionality has been confirmed by electrophysiological analysis. Interestingly, a recent in-depth examination of the electrophysiological profiles of human induced neuronal cells generated by lentiviral vector expression of BAM, Olig2, and Zic1 has revealed that the conversion of fibroblasts to neuronlike cells is incomplete, with passive membrane properties comparable to that of highly immature neurons [86] . However, the induced neuronal cells used in this study were sourced from research that has since been retracted, thus questioning the validity of these results.…”
Section: Generation Of Induced Neuronal Cellsmentioning
confidence: 99%
“…The neurophysiological development of the direct conversion of mouse-derived or neonatal human-derived somatic cells appears to follow a similar path to iPSC-derived neurons, with reports of AP firing cells as early as 8 days after transduction [ 99 , 101 , 105 , 117 ]. However, when transducing somatic cells from adult human tissue, up to 8 weeks are required to obtain neuronal cells capable of AP generation and the number of cells that fire multiple APs remains low [ 97 , 101 , 108 ]. Table 3 presents an overview of recent electrophysiological characterizations of human induced neurons.…”
Section: Functional Neuronal Circuits In a Dish: What We Have Found Fmentioning
confidence: 99%
“…Table 3 presents an overview of recent electrophysiological characterizations of human induced neurons. In the limited number of adult human iN cells capable of firing APs, the AP properties were shown to be highly variable, with broad FWHMs (>6 milliseconds), and most cells only fired single APs [ 108 ]. Importantly, it appears that human iN cells derived from adult somatic cells are not viable for long periods of time [ 118 ], making it difficult to culture human iN neuronal cells to functional maturity.…”
Section: Functional Neuronal Circuits In a Dish: What We Have Found Fmentioning
confidence: 99%
“…The passive electrophysiological properties of differentiating neurons also show characteristic changes. Membranes hyperpolarize to between -60 and -70 millivolts (mV) [135][136][137] , capacitance increases to 20-50 picoFarards (pF) 134,[138][139][140] , and input resistance decreases from around 4 gigaOhms (GΩ) to just over 1 GΩ 134,[138][139][140] in conjunction with development of active signaling and βIII-tubulin expression.…”
Section: Study Rationalementioning
confidence: 99%
“…Whether epSPCs from uninjured spinal cords require longer incubations in the current concentrations of differentiation agents, or whether they simply will never develop action potential firing and network activity amongst themselves without inputs from pre-existing mature neuronal circuitry, is still to be elucidated. The latter is unlikely, as this would make them unique not only from their rodent counterparts 58,67 , but also from iPSCs 139,149 , hESCs 132,140,150,156-and/or neurons may be useful in future to expedite maturation. Indeed, neurons from human iPSCs co-cultured with either cell type achieved mature physiological neuronal characteristics significantly faster than when cultured alone 161 .…”
Section: Passive Membrane Properties Do Not Change With Ticmentioning
confidence: 99%